NTRK‐rearranged spindle cell neoplasms are ubiquitous tumours of myofibroblastic lineage with a distinct methylation class. Issue 4 (12th December 2022) - Tauziède‐Espariat, Arnault; Duchesne, Mathilde; Baud, Jessica; Le Quang, Mégane; Bochaton, Dorian; Azmani, Rihab; Croce, Sabrina; Hostein, Isabelle; Kesrouani, Carole; Guillemot, Delphine; Pierron, Gaëlle; Bourdeaut, Franck; et al.
Abstract : Aims: NTRK gene fusions have been described in a wide variety of central nervous system (CNS) and soft tissue tumours, including the provisional tumour type 'spindle cell neoplasm, NTRK‐ rearranged' (SCN–NTRK), added to the 2020 World Health Organisation Classification of Soft Tissue Tumours. Because of histopathological and molecular overlaps with other soft tissue entities, controversy remains concerning the lineage and terminology of SCN–NTRK. Methods and results: This study included 16 mesenchymal tumours displaying kinase gene fusions ( NTRK fusions and one MET fusion) initially diagnosed as infantile fibrosarcomas (IFS), SCN–NTRK and adult‐type fibrosarcomas from the soft tissue, viscera and CNS. We used immunohistochemistry, DNA methylation profiling, whole RNA‐sequencing and ultrastructural analysis to characterise them. Unsupervised t ‐distributed stochastic neighbour embedding analysis showed that 11 cases (two CNS tumours and nine extra‐CNS) formed a unique and new methylation cluster, while all tumours but one, initially diagnosed as IFS, clustered in a distinct methylation class. All the tumours except one formed a single cluster within the hierarchical clustering of whole RNA‐sequencing data. Tumours from the novel methylation class co‐expressed CD34 and S100, had variable histopathological grades and frequently displayed a CDKN2A deletion. Ultrastructural analyses evidenced a myofibroblastic differentiation. Conclusions: Our findings confirm that SCN‐NTRK share similar features in adults and children and in all locations combine an infiltrative pattern, distinct epigenetic and transcriptomic profiles, and ultrastructural evidence of a myofibroblastic lineage. Further studies may support the use of new terminology to better describe their myofibroblastic nature. Abstract :